Physical and mathematical model of the processes of a device for processing watermelons - A. E. Nazimbekova; D. A. Tlevlessova; A. E. Kayrbaeva (Алматы технологиялық университетінің хабаршысы, 2022)
The knowledge of the grinding processes of the pulp of fruits and vegetables is not sufficient. In this article, we examined the processes of destruction, grinding, mixing the pulp of watermelon. The criterion equations of these processes are derived taking into account the indicators of the pulp and peel of the watermelon. The derivation of criteria equations for calculating the characteristics of the processes used in the processing of watermelon fruits is considered. The mechanic-technological basis for calculating and designing machines for processing watermelons for food purposes is outlined. The results of experimental studies to determine the optimal kinematic and structural parameters of these machines are presented. The basic physic mechanical and rheological properties of watermelon fruits are given. One of the tasks set for the researcher was to choose a physical model of the processes of separation of pulp from the crust, destruction, grinding of pulp and mixing of the pulp. The values of these quantities depend both on the kinematic parameters of the dynamic interaction and on the physic mechanical and rheological properties of the fruits of melons. The obtained criteria equations can be used to determine the technological parameters of machines where it is necessary to destroy the fetus with minimal energy costs.